Pengaruh Switching Cost sebagai Pemoderasi Hubungan antara Kepuasan dan Loyalitas Konsumen - Aditya Putranto Ardhani (Jurnal Riset Manajemen dan Bisnis, 2007)
The aim of this research is to exornine the moderating effect of switching cost on the relationship between customer satisfaction"ia-ioyaiy. The reiearch object is 150 customers who use mobile phone Sim Card in Yogtakarta. The result shows that the moderating effect of switching cost on the relationship between satisfaction and loyatty is not supported. However the ffict ;f customer satisfaction on loyalty persists with or without the switching cost.Keywords: Switching Cost, Customer Satisfaction, Customer Loyalty